Venom Gene Sequence Diversity and Expression Jointly Shape Diet Adaptation in Pitvipers. (13th April 2022) - Mason, Andrew J.; Holding, Matthew L.; Rautsaw, Rhett M.; Rokyta, Darin R.; Parkinson, Christopher L.; Gibbs, H. Lisle
Abstract: Understanding the joint roles of protein sequence variation and differential expression during adaptive evolution is a fundamental, yet largely unrealized goal of evolutionary biology. Here, we use phylogenetic path analysis to analyze a comprehensive venom-gland transcriptome dataset spanning three genera of pitvipers to identify the functional genetic basis of a key adaptation (venom complexity) linked to diet breadth (DB). The analysis of gene-family-specific patterns reveals that, for genes encoding two of the most important venom proteins (snake venom metalloproteases and snake venom serine proteases), there are direct, positive relationships between sequence diversity (SD), expression diversity (ED), and increased DB. Further analysis of gene-family diversification for these proteins showed no constraint on how individual lineages achieved toxin gene SD in terms of the patterns of paralog diversification. In contrast, another major venom protein family (PLA2 s) showed no relationship between venom molecular diversity and DB. Additional analyses suggest that other molecular mechanisms—such as higher absolute levels of expression—are responsible for diet adaptation involving these venom proteins. Broadly, our findings argue that functional diversity generated through sequence and expression variations jointly determine adaptation in the key components of pitviper venoms, which mediate complex molecular interactions between the snakes and their prey.